Investigation and correlation between surface modifications and field emission properties of laser-induced silicon plasma ion irradiated stainless steel. Issue 7 (3rd August 2022) - Amir, Rizwan; Bashir, Shazia; Akram, Mahreen; Rafique, Muhammad Shahid; Javed, Mubashir; Mahmood, Khaliq; Husinsky, Wolfgang; Ahmad, Shahzeb
Abstract : Laser-induced silicon (Si) plasma has been used as a source of ion irradiation for modifications in surface, structural and field emission properties of Stainless Steel (SS). Nd:YAG (532 nm, 10 ns) laser at irradiance of 15 GW/cm 2 was used to generate Si-plasma ions which were detected by solid-state nuclear track detector (CR-39) and Faraday Cup (FC). Both the energy and fluence of Si ions were measured by FCs. In response to a stepwise increase in the number of laser pulses from 3000 to 12000, the ion fluence varies from 4.6 × 10 14 to 18.3 × 10 14 ions/cm 2 with constant energy of 30 keV. Fourier Transformation Infrared (FTIR) spectroscopy analysis revealed that irradiated silicon makes the stretch band with oxygen Si–O–Si. X-Ray Diffraction (XRD) analysis confirmed the identification of new phase of Si (111) with an anomalous trend in crystallite size, dislocation line density and induced stresses in response to the irradiation with various Si ion fluences. Optical microscopy analysis showed the formation of pits, voids and tracks. Scanning electron microscope (SEM) analysis revealed the formation of nanoscale surface features including pores, craters, embedded particulates and protruded disk-like structures with multiple ablative layers at the fluence of 4.6 × 10 14 to 13.7 × 10 14 ions/cm 2 . At the highest ion fluence of 18.3 × 10 14 ions/cm 2, the flake/flower-like morphology is observed. Field emission (FE) properties were studied under ultra-high vacuum condition in a parallel plate conﬁguration using planar virgin SS as an anode and structured SS as a cathode. The Fowler–Nordheim plots were obtained from I–V characteristics to evaluate the turn-on field, field enhancement factor β and a maximum current density ranging 1.5–4.5 V/µm, 5008–12807 and 96–454 nA/cm2, respectively. The variation in the FE properties is attributed to the different morphological features at varying silicon ion fluences.